Optimization of SIS solar cells with ultra-thin silicon oxide layer - Song, X. M.; Ye, C. Y.; Huang, Z. G. (Frontiers in Energy Research, 2023)
Due to the simple process, low energy consumption and stable performance, semiconductor/insulating layer/semiconductor (SIS) solar cells have attracted lots of research interests. However, the device physics of SIS solar cells needs further clarification and improvement. In this paper, the effects of TCO work function on the performance of TCO/SiO2/n-Si heterojunction solar cells were simulated by AFORS-HET and the physics mechanisms for these effects were clarified. It is found that for a work function of 5.2 eV or higher of TCO, the SIS devices possess high ƞ of 22.9% or higher, while the devices show the S-shape J-V curve with low FF when the work function work function of TCO is under 5.1 eV. Further analysis indicates that the work function difference between TCO and n-Si substrate is so small that there is an insufficient band bending at the interface leading to a lower built-in electric field that degrades the photogenerated carriers' separation, which results in the deformation of J-V curve. Moreover, the simulation results show that the performances of TCO/SiOx/n-Si devices are significantly affected by the band offsets at the SiOx/n-Si interface. When the conduction band offset is higher than 0.4 eV, it can effectively prevent electrons from passing through the SiOx layer to reduce the recombination at the interface, resulting in the excellent output performances of the SIS device. But for a low conduction band order of 0.4 eV or less, the blocking effect of electrons weakens, leading to the large recombination at the interface. Finally，we propose two mechanisms of S-shape J-V curve of SIS solar cells: one is the built-in electric field is too small to separate photogenerated carriers, and the other one is that the carrier transmission is blocked by the thick tunneling layer or insulating layer. This work deepens the understanding of the device physics of SIS solar cells and paves the way for enhancing the output performance of industrial Si-based solar cells.